1992
DOI: 10.1007/bf00974574
|View full text |Cite
|
Sign up to set email alerts
|

On the activity of ?-aminobutyric acid and glutamate transporters in chick embryonic neurons and rat synaptosomes

Abstract: The uptake of radioactive gamma-aminobutyric acid (GABA) and D-aspartate and the effect of SKF 89976-A, a non-substrate inhibitor of the GABA transporter, on this uptake have been investigated. Neuronal cultures from eight-day-old chick embryos grown for three or six days in vitro, were used as a model. For comparison, we also used the P2-fraction from rat. Neuronal cultures grown for three and six days expressed high-affinity uptake systems for [3H]GABA and for D-[3H]aspartate with an increasing Vmax during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…1, C and D, shows that the increase in transport following extracellular GABA treatment is both concentration-dependent and time-dependent. A logistic fit to the concentrationresponse data estimates an EC 50 for up-regulation by GABA to be approximately 5 M, which is comparable to the K m values for GABA uptake in both brain tissue (27,28) and in cells heterologously expressing GAT1 (23,26,29). Additionally, maximal up-regulation of uptake occurred with 30 min of pretreatment with 100 M GABA.…”
Section: Resultssupporting
confidence: 53%
“…1, C and D, shows that the increase in transport following extracellular GABA treatment is both concentration-dependent and time-dependent. A logistic fit to the concentrationresponse data estimates an EC 50 for up-regulation by GABA to be approximately 5 M, which is comparable to the K m values for GABA uptake in both brain tissue (27,28) and in cells heterologously expressing GAT1 (23,26,29). Additionally, maximal up-regulation of uptake occurred with 30 min of pretreatment with 100 M GABA.…”
Section: Resultssupporting
confidence: 53%
“…In the case of GABA, in which ''high-affinity'' transport is located predominantly in neurons, it is actually expressed more strongly in the developing, as compared to the adult, nervous tissue (for a review, see Balcar and Johnston, 1987). Developmental time course of EAA transport in nervous tissue has not been studied in the same detail as that of GABA transport (except in culture: Yu et al, 1984;Lewin et al, 1992), but it has been demonstrated that [ 3 H]L-glutamate is strongly accumulated by neuronal perikarya well before the formation of most of the excitatory synapses, at least in the rat hippocampus (Schmidt and Wolf, 1988). Since, in the adult hippocampus, glutamate transporters are located predominantly in glial cells (Rothstein et al, 1994;Lehre et al, 1995) those findings (Schmidt and Wolf, 1988) suggest a specific role 1 antibody (B), showing co-localisation between the neuronal marker NF200, and the glutamate transporter GLT-1.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous paper we studied the effect of SKF 89976-A on the ['HIGABA release from 6d-old primary neuronal cultures made from embryonic chick telencephalon (Lewin et al 1992a). The potassium stimulated ['HIGABA release from these relatively young cultures was not calcium dependent, indicating that no or few synaptic vesicles are developed at day six in vitro (Lewin et al 1992a). The present study was made with a more mature culture.…”
mentioning
confidence: 99%